DNA polymerases as useful reagents for biotechnology – the history of developmental research in the field - Ishino, Sonoko; Ishino, Yoshizumi (Frontiers in Microbiology, 2014)
DNA polymerase is a ubiquitous enzyme that synthesizes complementary DNA strands according to the template DNA in living cells. Multiple enzymes have been identified from each organism, and the shared functions of these enzymes have been investigated. In addition to their fundamental role in maintaining genome integrity during replication and repair, DNA polymerases are widely used for DNA manipulation in vitro, including DNA cloning, sequencing, labeling, mutagenesis, and other purposes. The fundamental ability of DNA polymerases to synthesize a deoxyribonucleotide chain is conserved. However, the more specific properties, including processivity, fidelity (synthesis accuracy), and substrate nucleotide selectivity, differ among the enzymes. The distinctive properties of each DNA polymerase may lead to the potential development of unique reagents, and therefore searching for novel DNA polymerase has been one of the major focuses in this research field. In addition, protein engineering techniques to create mutant or artificial DNA polymerases have been successfully developing powerful DNA polymerases, suitable for specific purposes among the many kinds of DNA manipulations. Thermostable DNA polymerases are especially important for PCR-related techniques in molecular biology. In this review, we summarize the history of the research on developing thermostable DNA polymerases as reagents for genetic manipulation and discuss the future of this research field.